Etika dan Tanggung Jawab dalam Menguatkan Kesalehan Sosial di Bulan Ramadhan dalam Kegiatan Bersedekah - Supriyanti, Tuti; Sanusi, Anwar (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2024)
Social piety is a collective responsibility, where we all play a role in fostering goodness both for ourselves and our surroundings. Individual piety is often referred to as habluminallah, while social piety is known as habluminannas. Piety is usually associated with religion, namely people who are devout in practicing religious teachings. One highly recommended good deed in Islam is giving alms, especially during the month of Ramadan, in addition to observing the fast. Muslims are encouraged to increase their good deeds, such as giving alms, during this holy month. Responsibility is inherent, meaning it is a natural part of human life; everyone inevitably has responsibilities. If someone neglects their responsibilities, others will compel them to fulfill them. Therefore, responsibility can be viewed from two sides: the side of the doer and the side of the interest of others. This article aims to strengthen social piety in the community, particularly through giving alms during Ramadan. The method used is a literature review. In conclusion, social piety can be naturally achieved in conjunction with the performance of maghdhah and ammah worship, as these acts of worship encompass all aspects of human behavior.